Replicating Studies in Which Samples of Participants Respond to Samples of Stimuli. (May 2015) - Westfall, Jacob; Judd, Charles M.; Kenny, David A.
In a direct replication, the typical goal is to reproduce a prior experimental result with a new but comparable sample of participants in a high-powered replication study. Often in psychology, the research to be replicated involves a sample of participants responding to a sample of stimuli. In replicating such studies, we argue that the same criteria should be used in sampling stimuli as are used in sampling participants. Namely, a new but comparable sample of stimuli should be used to ensure that the original results are not due to idiosyncrasies of the original stimulus sample, and the stimulus sample must often be enlarged to ensure high statistical power. In support of the latter point, we discuss the fact that in experiments involving samples of stimuli, statistical power typically does not approach 1 as the number of participants goes to infinity. As an example of the importance of sampling new stimuli, we discuss the bygone literature on the risky shift phenomenon, which was almost entirely based on a single stimulus sample that was later discovered to be highly unrepresentative. We discuss the use of both resampled and expanded stimulus sets, that is, stimulus samples that include the original stimuli plus new stimuli.